A systematic review of the present and future of non-alcoholic fatty liver disease - Lucas, Christiana; Lucas, Georgia; Lucas, Nicholas; Krzowska-Firych, Joanna; Tomasiewicz, Krzysztof (Clinical and Experimental Hepatology, 2018)
Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in the Western world. Ongoing research has furthered our understanding of NAFLD, the nature of progression of this disease, and its impact on morbidity and mortality. An active form of NAFLD is non-alcoholic steatohepatitis (NASH); it is the most severe subtype, without any current recommended therapies, according to the European Medicines Agency. The development of new therapies presents challenges, notably due to the slow progression of NASH and the clinically relevant endpoints. Correlating new data with effective treatment regimens is an emerging challenge, which will increase our understanding of the factors affecting the NAFLD course. This can enable more appropriate non-invasive prognostic assessments, which can focus on specifically at-risk NAFLD populations for tailored individual treatment. This review article aims to highlight the current developments in the field of NAFLD: pathogenesis, epidemiology, diagnosis, clinical features, and available treatment, including novel targets and therapies.